The transformation of the nuclear law of the Russian Federation into an independent public complex branch of law as a way to strengthen global nuclear security in the world - Kornienko, V. T.; Makeeva, O. A.; Bragina, E. A. (Глобальная ядерная безопасность, 2024)
This article considers the process of transformation of the Russian Federation nuclear law into an independent public complex branch of law and its important role in improving global nuclear safety. Since it is well known that the criteria of distinguishing branches of law are usually the subject and method of legal regulation as well as the existence of their own codification, the authors are confident of such a need. The results of the analysis of the state corporation Rosatom activities serve as the basis for the proposed theses and only confirm this confidence. The main idea of the article is to assert the need for changes in the Russian legal system structure in order to increase the effectiveness of regulation in the field of nuclear safety. The paper examines the evolution of nuclear law in Russia, identifies the basic principles and norms of this area of law as well as the need to make changes to adapt to modern challenges and threats. Supporting its position by analyzing the current state of the Russian nuclear industry and world standards in the field of nuclear safety, the article suggests practical steps to strengthen legal regulation to ensure safety in the nuclear field. Special attention is paid to the importance of strengthening international nuclear safety through the modernization of the national nuclear legal system, its compliance with international norms and standards. The article discusses current issues, including the development of nuclear doctrine, control of nuclear materials, responsibility for violation of international nuclear obligations and other aspects affecting global nuclear security. The study is an important contribution to understanding the problems of nuclear law in the context of global safety, and also substantiates the need for independent development of this branch of law to ensure stability and security on the world stage. The authors of the article offer specific recommendations for improving legislation and practice in the field of nuclear law in order to strengthen global nuclear safety